Dinâmica de uso e cobertura da terra e potencial de transição agricultura convencional – agroecológica: estudo de caso da Bacia Hidrográfica do Rio Itaporanga – Barcarena - Pará - SILVA JÚNIOR, Osmar Guedes da (2020)
Knowledge about land use and land cover represents an important tool for environmental monitoring and planning and in this context, the watershed must be understood as a system of relationships in nature and how anthropic actions are interconnected. In this way, the adoption of agroforestry systems (SAFs) as land use and land cover systems to replace conventional agriculture becomes essential. This work aimed to analyze the use of land use and land cover and the potential for implementing systems agroforestry in the watershed Itaporanga River, municipality of Barcarena-PA. To achieve these objectives, data from the agricultural sectors of 2005 and 2016 were used, medium-resolution images Landsat 5 and Landsat 8 from the years 1984, 1994, 2004, 2013 and 2019, current images (09/09/2019) of high resolution Google Earth, as well as fieldwork for validation. A quantitative analysis of the IBGE data showed that there was an increase, from 2005 to 2016, of 59.39% (1319 ha) of areas planted or collected for the main products of temporary and permanent crops in the municipality of Barcarena. Using the MAXVER supervised classification technique on medium resolution images, four classes of use and coverage were identified: Water, Forest, Cultivation and / or area prepared for cultivation and Exposed Soil. The results of this analysis show a constant reduction in forest cover, giving space to cultivated and urbanized areas, the latter mainly increased by urban expansion in the municipality, as a result of the implantation of industrial centers in the early 1980s. A visual analysis from the application of a key interpretation key in the high resolution images allowed the discrimination of eight saber classes: Forest, Pasture, Capoeira, Urbanized Areas, Cultivation, Intended for cultivation, Exploration / Degraded Areas and Exposed Soil. Among these classes are areas currently occupied by Capoeira, Areas of exploitation / Degradation and exposed soil, in addition to pastures that are used as an application for the implementation of agroforestry systems.